2014
DOI: 10.1371/journal.pone.0112043
|View full text |Cite
|
Sign up to set email alerts
|

Plasma MicroRNAs as Potential Noninvasive Biomarkers for In-Stent Restenosis

Abstract: ObjectiveTo investigate whether microRNAs (miRs) can serve as novel biomarkers for in-stent restenosis (ISR).MethodsThis retrospective, observational single-centre study was conducted at the cardiovascular department of a tertiary hospital centre in the north of China. Follow-up coronary angiography at 6 to 12 months was performed in 181 consecutive patients implanted with drug-eluting stents. Fifty-two healthy volunteers served as the control group. The plasma miRs levels were analyzed by quantitative real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 46 publications
1
38
1
Order By: Relevance
“…*P < 0.01, **P < 0.001. er candidate. miR-21 has been previously described as a biomarker for atherosclerosis and heart transplant rejection and in multiple cancers (22,24,25,45,46). We found that plasma miR-21 increased early during the stage of diastolic dysfunction and positively correlated with the degree of tissue fibrosis.…”
Section: Figure 4 Rv Mir-21 Is Upregulated In Children With Pi+ps Anmentioning
confidence: 53%
See 1 more Smart Citation
“…*P < 0.01, **P < 0.001. er candidate. miR-21 has been previously described as a biomarker for atherosclerosis and heart transplant rejection and in multiple cancers (22,24,25,45,46). We found that plasma miR-21 increased early during the stage of diastolic dysfunction and positively correlated with the degree of tissue fibrosis.…”
Section: Figure 4 Rv Mir-21 Is Upregulated In Children With Pi+ps Anmentioning
confidence: 53%
“…Circulating miRs in body fluids have been described as biomarkers of cardiovascular disease and cancer progression (21)(22)(23). We therefore evaluated the expression of the upregulated RV profibrotic miRs in plasma to evaluate their usefulness as potential biomarkers of fibrosis in the RV.…”
Section: Model Of Pi+ps Recapitulates the Clinical Setting -Early Diamentioning
confidence: 99%
“…Molecular aspects gave rise to analyses investigating miRNAs as biomarkers for in-stent restenosis [40,[112][113][114]. Indeed, circulating miR-21, miR-143, miR-145, and miR-100 were reported to be dysregulated in ISR patients compared with control patients without ISR after drug eluting stent implantation [115]. A recent study confirmed dysregulated circulating miR-21 levels in pig and mouse models after coronary stenting [116].…”
Section: Mirnas As Biomarkers In Additional Entities Of Cardiovasculamentioning
confidence: 99%
“…These signalling pathways are central mediators of the vascular remodelling process following acute injury, regulating VSMC proliferation, migration, and phenotype [35]. Similar to the Ji et al study described above, upregulation of miR-21 has been observed across many in vivo models of vascular injury, including mouse and pig models of vein graft failure, and mouse models of ISR [29] showed that miR-21 could act as a potential biomarker for the development of ISR [39]. In PAH, manipulation of miR-21 levels has also been shown to affect the vascular remodelling that leads to the formation of obstructive lesions in the pulmonary vasculature.…”
Section: The Role Of Mirnas In Pathological Vascular Remodellingmentioning
confidence: 63%